Calorimetric Measurements of the Output Power of the 2.48 GHz Commercial Magnetron - Rosario, Leo Mendel; Tumlos, Roy (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
A 2.45 GHz magnetron from a domestic microwave oven, with a power output rating of 1.5 kW, is utilized as the microwave source in the design of a multipurpose electron cyclotron resonance plasma device in the Plasma Physics Laboratory of the National Institute of Physics. Measurements of the power output to a 2 liter water load and a dummy load were obtained using calorimetry. The experiment shows that it is possible to achieve a relatively stable maximum average power of 190 W delivered to the 2 liter water load continuously for at least 10 min. It is also shown that the magnetron can deliver a maximum power of about 2.2 kW.